Whole-exome sequencing in multiplex preeclampsia families identifies novel candidate susceptibility genes - Melton, Phillip; Johnson, M.; Gokhale-Agashe, D.; Rea, A.; Ariff, A.; Cadby, G.; Peralta, J.; Mcnab, T.; Allcock, R.; Abraham, L.; Blangero, J.; Brennecke, S.; et al. (Lippincott Williams & Wilkins, 2019)
OBJECTIVE: Preeclampsia is a common and serious heritable disorder of human pregnancy. Although there have been notable successes in identification of maternal susceptibility genes a large proportion of the heritability of preeclampsia remains unaccounted for. It is has been postulated that rare variation may account for some of this missing heritability. In this study, we performed whole-exome sequencing (WES) in multiplex families to identify rare exonic risk variants. METHODS: We conducted WES in 244 individuals from 34 Australian/New Zealand multiplex preeclampsia families. Variants were tested for association with preeclampsia using a threshold model and logistic regression. RESULTS: We found significant association for two moderately rare missense variants, rs145743393 (Padj = 0.0032, minor allele frequency = 0.016) in the chromosome 1 open reading frame 35 (C1orf35) gene, and rs34270076 (Padj = 0.0128, minor allele frequency = 0.024) in the pyroglutamylated RFamide peptide receptor (QRFPR) gene. To replicate these associations we performed imputation in our Australian genome wide association scan for preeclampsia and found no significant exonic variants in either C1orf35 or QRFPR. However, 11 variants demonstrating nominal significance (P < 0.05) in the genomic region between QRFPR and annexin A5 (ANXA5) were identified. We further leveraged publicly available genome-wide available summary data from the UK Biobank to investigate association of these two variants with the underlying clinical phenotypes of preeclampsia and detected nominal association of the QRFPR variant (rs34270076, P = 0.03) with protein levels in females. CONCLUSION: The study represents the first to use WES in multiplex families for preeclampsia and identifies two novel genes (QRFPR and C1orf35) not previously associated with preeclampsia and find nominal association of rs34270076 with protein levels, a key clinical feature of preeclampsia. We find further support for ANXA5 previously associated with pregnancy complications, including preeclampsia.